2023
DOI: 10.1007/s12649-023-02074-y
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Valorization of Wood Residue for the Production of Biofuel Materials Via Continuous Flow Hydrothermal Liquefaction

Abstract: Almost half of the wood resulted from mass deforestation for infrastructure and agricultural developments is declared waste. To mitigate the impact and exploit renewable sources of energy sustainably it is paramount to explore their further utilizations. Hydrothermal liquefaction (HTL) technology holds the promise to convert biomass into biofuels. In this study, conversion of wood residue under continuous flow, subcritical HTL was investigated under two conditions; untreated and alkaline pretreated. Results sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The HTL system and the biomass samples utilized for data generation were previously described in ref. 10. For the experimental setup, both cotton and dissolved glucose were employed to create comparable HTL aqueous streams.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HTL system and the biomass samples utilized for data generation were previously described in ref. 10. For the experimental setup, both cotton and dissolved glucose were employed to create comparable HTL aqueous streams.…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary study focusing on the conversion of pre-treated wood waste residues has demonstrated that continuous flow HTL can achieve glucose NER values as high as 63%. 10 To enhance the optimization of biomass conversion in continuous flow HTL, additional studies are required to refine parameters optimization, biomass load-to-weight ratio, and pre-treatment methods. Nevertheless, the rapid optimization of biomass conversion in continuous flow HTL encounters two primary challenges.…”
Section: Introductionmentioning
confidence: 99%